2012
DOI: 10.1007/s00268-012-1447-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Profile, Airway Management, and Outcome in Huge Multinodular Goiters: An Institutional Experience from an Endemic Goiter Region

Abstract: Long-standing huge goiters are common in iodine-deficient endemic areas. The majority of patients have symptomatic or clinicoradiological evidence of airway involvement. The incidence of RSE, airway deformity, intubation difficulty, and tracheomalacia is high with huge goiters. The surgery is technically demanding with greater associated chances of injury to native structures. Malignancy influences the presentation and outcome in smaller goiters. In centers with experienced endocrine surgeons and dedicated ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 22 publications
7
38
0
Order By: Relevance
“…The analysis of primary diagnosis in the group of patients with DI showed that the highest number of DI were present in the group of patients with multinodular goiter, followed by the group with hyperthyroidism and those with cancers, and the least in the group with nodular goiter. Since patients with multinodular goiters, as a rule, have maximum dimension of goiter, and those with nodular goiters the least thyroid size, this indirectly proves that the size of goiter has the largest share in DI occurrence, as shown by the results of a recent study by Agarwal et al 16 . The circumference and length of the neck in our study were singled out as one of the most important risk factors for DI and as an independent predictor of DI in thyroid surgery.…”
Section: Nevena Kalezić Et Alsupporting
confidence: 51%
“…The analysis of primary diagnosis in the group of patients with DI showed that the highest number of DI were present in the group of patients with multinodular goiter, followed by the group with hyperthyroidism and those with cancers, and the least in the group with nodular goiter. Since patients with multinodular goiters, as a rule, have maximum dimension of goiter, and those with nodular goiters the least thyroid size, this indirectly proves that the size of goiter has the largest share in DI occurrence, as shown by the results of a recent study by Agarwal et al 16 . The circumference and length of the neck in our study were singled out as one of the most important risk factors for DI and as an independent predictor of DI in thyroid surgery.…”
Section: Nevena Kalezić Et Alsupporting
confidence: 51%
“…Fibrosis, another component of the TDS, is seen in Hashimoto’s thyroiditis, and contributes to higher complication rates (12). Finally, larger gland size contributes to higher complication rates, specifically airway complications and transient hypocalcemia (13, 15, 24). The TDS incorporates all of these aspects of difficulty—size, vascularity, friability, and gland size—to create a single composite score of difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Among this number, only 20 (0.67%) were described as presenting with acute airway problems requiring emergency intervention, attributed to either severe luminal compression, intrathyroidal haemorrhage or upper respiratory infection. In a retrospective review of 813 cases of total thyroidectomy in India by Agarwal et al ,7 data analysis included a comparison between malignant and benign goitres with regard to respiratory distress. They noted a significantly higher rate of respiratory distress in malignant goitres among those weighing ≤400 g (5.3% vs 1.9%, p=0.013), and a slight but insignificantly increased rate among those over 400 g (40% vs 20%, p=0.15).…”
Section: Discussionmentioning
confidence: 99%